The militarization of the alhashd alshaebi and its representations in contemporary Iraqi art - تقي, سارة (Basrah Arts Journal, 2025)
Search summary: This research monitors the topic of the militarization of the Popular Mobilization Forces in Iraqi society and how it is represented in contemporary Iraqi painting. The research is divided into four chapters. The first chapter is devoted to stating the research problem, which is defined as highlighting the concept of militarization in society, especially the militarization of the Popular Mobilization Forces and how it is represented in contemporary Iraqi painting and the extent to which it is affected by the militarization that its society has been exposed to, the importance of the research and the need for it. The research aims to clarify the extent to which contemporary Iraqi painting is affected by the militarization of the Popular Mobilization Forces, and how this militarization has affected the styles of contemporary Iraqi artists. As for the second chapter, it consists of two sections and previous studies and their discussion, as well as extracting and discussing the indicators of the theoretical framework to benefit from them in formulating the research performance. The first section was about the concept of militarization, while the second section focused on the militarization of the Popular Mobilization Forces and explained its starting points, types and objectives, in addition to its causes and discussing these causes. As for the third chapter, it included the research procedures, as it identified the research community and selected the sample, then reviewed the treatments for the research tool and the method of constructing it and analyzing the slave. The fourth chapter included the research results and conclusions.